Real-time daylight glare control using a low-cost, window-mounted HDRI sensor. (15th June 2020) - Kim, Michael; Konstantzos, Iason; Tzempelikos, Athanasios
Abstract: The main limitation of existing daylight glare control strategies is their fundamental inability to efficiently identify the location, size and brightness of potential glare sources in real-time. This study presents a new daylight glare control framework, using a low-cost, window-mounted programmable High Dynamic Range Image (HDRI) sensor with a wide fisheye lens. With proper calibration, the sensor can accurately measure the luminance, size, and relative position of any exterior glare sources in real time, using per pixel analysis. We present a method to enable reliable solar-tracking and an efficient glare source positioning algorithm, which can also detect glare sources of small size but significant luminance (e.g., intense reflections from surroundings). Complications due to the occupant position relative to the sensor/source are also discussed. The HDRI-based glare control was implemented in a private office with automated roller shades and was also compared with two common glare controls under the same sky conditions. The experimental results showed that the HDRI-based glare control can continuously and fully protect from detected glare sources, maintaining visual comfort, whereas the other controls failed in certain instances or are over-conservative. This new framework is the first proposed solution to address direct and reflective glare in a straightforward and efficient way, and it can be used as an extra layer in existing daylighting controls for glare mitigation. This technology can be used in the future to fully replace photometer-based fenestration controls and additional sensors, as well as to learn occupant visual preferences associated with exterior conditions. Highlights: Daylight glare control framework using a low-cost, programmable HDRI sensor. Reliable solar-tracking and efficient glare source positioning algorithm. The HDRI-based glare control can continuously protect from glare sources. Developed to address direct and reflective glare in an efficient way. Can replace photometer-based fenestration controls and additional sensors.